THE MILITARY PROFESSION AND CHRISTIAN ETHICS - Nifon MIHĂIȚĂ (Annals: Series on Military Sciences, 2009)
Generation after generation, man has sought to base his life on certainties and to express confidence in commitment to those institutions providing stability and safety. Thus, not accidentally, at least in contemporary Romania, the Church and the Army enjoy great trust and are considered two fundamental institutions of our society.